(untitled) (Studia austriaca, 2024)
The writer and journalist Paul Goldmann (1865-1935) was one of Arthur Schnitzler’s closest friends. At the same time, he represents the greatest friendship break in Schnitzler’s life. The correspondence between Goldmann and Schnitzler from 1888 to 1931 provides a better understanding not only of Goldmann’s biography, but also of his difficult relationship with Schnitzler.